Strong Photoacoustic Signal Enhancement by Coating Gold Nanoparticles with Melanin for Biomedical Imaging. (15th December 2017) - Repenko, Tatjana; Rix, Anne; Nedilko, Alexander; Rose, Jonas; Hermann, Alina; Vinokur, Rostislav; Moli, Sheila; Cao‐Milàn, Roberto; Mayer, Martin; von Plessen, Gero; Fery, Andreas; De Laporte, Laura; et al.
Abstract: Photoacoustics is a powerful biomedical imaging and detection technique, because it is a noninvasive, nonionizing, and low‐cost method facilitating deep tissue penetration. However, suitable contrast agents need to be developed to increase the contrast for in vivo imaging. Gold nanoparticles are often discussed as potential sonophores due to their large absorption cross‐section and their tunable plasmon resonance. However, disadvantages such as toxicity and low photoacoustic efficiency in the tissue transparency window prevail, preventing their clinical application. As a result, there remains a strong need to develop colloidal photoacoustic contrast agents which absorb in the tissue transparency window, exhibit high photoacoustic signal, and are biocompatible. Here, a facile synthetic approach is presented to produce melanin shells around various gold nanoparticle geometries, from spheres to stars and rods. These hybrid particles show excellent dispersability, better biocompatibility, and augmented photoacoustic responses over the pure melanin or pristine gold particles, with a rod‐shape geometry leading to the highest performance. These experimental results are corroborated using numerical calculations and explain the improved photoacoustic performance with a thermal confinement effect. The applicability of melanin coated gold nanorods as gastrointestinal imaging probes in mouse intestine is showcased. Abstract : Here, the preparation of melanin coated gold particles is presented. The melanin coating provides enhanced colloidal stability, improved biocompatibility, and augmented photoacoustic contrast. The reasons for these improvements are analyzed experimentally and theoretically and it is found that a thermal confinement effect leads to enhanced photothermal efficiency, which is exploited for intestinal photoacoustic imaging.